Caracterização parcial de polissacarídeos sulfatados e aplicação como indutores de resistência pós-colheita em mangas e maçãs - Lima, Carlos Pinheiro Chagas de (2020)
In view of the population growth, the demand for food tends to increase. Today, growing food production in a way that is safe for health and the environment is a challenge. Elicitors are promising compounds to help solve this challenge, as they induce plant defense against phytopathogens, microorganisms that cause losses between 10 to 40% of the world's agricultural production yield. Ulvans and glucuronans are polysaccharides that can act as elicitors. The activity of these carbohydrates seems to be related to the sulfate groups and the residues of rhamnose and uronic acids. As chichá gum (GCH), a polysaccharide similar to karaya gum, contains residues of rhamnose and uronic acid, it was decided to make chemical modifications to this gum and perform tests to evaluate its ability to induce post-harvest resistance. The gum and derivatives had their identities confirmed by infrared spectroscopy. Thermal gravimetry indicated that the gum after being sulfated (GCHS) and deacetylated (GCHDA) became thermally more labile. The molar mass of all derivatives of chichá gum decreased after the modifications. The 13C-NMR revealed that there was sulfation in C6 of the galactose and in the rhamnose residue. Mangoes and apples were used to test the eliciting activity of the gums. The fruits were sprayed with the polysaccharide solutions and the activity of defense enzymes was measured using the commercial inducer Benzothiadiazole (BTH) as a positive control. GCHDA, and mainly GCHS, increased (p < 0.05) the activity of the enzyme guaicol peroxidase (GPX) in 12‒48 h, in apples. The PPO activity in the pulp of these GCHS treated fruits increased at 12 and 24 h (p < 0.05). This work suggests that polysaccharides from plant exudate may be a promising source of plant defense inducing compounds.